"From celebrities to the girl next door": Influencer marketing with a special focus on the social media platform, Instagram. - Valgerður Anna Einarsdóttir 1992- (2017)
There has been a lot of discussion about product placement, influencer marketing and advertising in general in the media. Celebrities, meaning famous actors, singers, athletes or politicians have been used by companies to generate popularity amongst products and experiences for years. Today, access to the Internet has never been greater and people are constantly connected online across various social media platforms, for example, Instagram. Since it launched in 2010, Instagram has attracted around seven hundred million users worldwide. Due to its popularity, no wonder it has caught the attention of marketers and advertising agencies. Now there seems to have been a shift, social media marketing is bigger than ever and influential individuals are emerging everywhere with what it seems, no global restrictions. Consumers can be vulnerable to advertising and be blindsided by the façade which can create a false need and desire. Companies have started to pay for Instagram posts on user profiles with a large following (exceeding one thousand people), how this affects the buying behavior of the basic consumer is interesting to find out. These influential users are changing the game of marketing. Whether it is a genuine review or if it is a paid opinion, that is open to interpretation by the individual affected. To aid in finding the answer to the research question a qualitative study was conducted. The objective of the study was not to find a concrete answer but to gain a deeper understanding of the subject at hand. How do Instagram users view these adverts and do they believe the opinion of an Instagram influencer more than the opinions of celebrities? Data was collected and analyzed by interviewing five individuals, all active on Instagram. They were between the ages of 18 – 29, both male and female. Even though the results are limited to Iceland, the key findings of the research were that there has been a shift from celebrities to social media personalities regarding effective influencer marketing on social media ...